Analysis of silicon incorporation into VGF-grown GaAs - Birkmann, Bernhard; Weingärtner, Roland; Wellmann, Peter; Wiedemann, B.; Müller, Georg (Journal of Crystal Growth, 2002)
The incorporation of silicon into VGF-grown GaAs is examined by Hall effect measurements, spark source mass spectrometry and photoluminescence (PL). It is found that the silicon is incorporated into the crystal according to Scheils-law with the Si concentration [Si] rising from 1.5 x 10(18) to 1 x 10(19) cm(-3). It is found that the intensity of the PL peak with energy close to the band gap decreases with increasing Si content of the material, whereas the intensity of the PL peak related to the acceptor SiGaVGa shows opposite behaviour. A compensation model which takes into account the acceptors Si-As and SiGaVGa is developed. The model describes the relationship between [Si] and the charge carrier concentration n up to silicon concentrations of 1 x 10(19) cm(-3) in GaAs grown under low thermal gradients. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: Doping; Point defects; Segregation; Semiconducting gallium arsenide

Das Neue geschieht an den Grenzflächen. - Schlücker, Eberhard; Müller, Georg; Wasserscheid, Peter (Chemie Ingenieur Technik, 2005)
UnivIS-Import:2015-03-09:Pub.2005.tech.ITC.prozma.dasneu

Growth rate control in SiC-physical vapor transport method through heat transfer modeling and non-stationary process conditions - Straubinger, Thomas; Bickermann, Matthias; Grau, M.; Hofmann, Heinz-Dieter; Kadinski, Lev; Müller, Georg; Selder, Markus; Wellmann, Peter; Winnacker, Albrecht (Materials Science Forum, 2000)
The thermal data used were determined from pyrometrical measurements on the top and bottom of the crucible during the experiments and were combined with simulations of the 2-dimensional heat transfer in the assembly. The latter allowed us to obtain the temperatures (source, crystal) inside the reaction chamber which were not assessable by direct measurement
Keywords: Heat Transfer; Mass Transport; Non-Stationary Process

Quantitative determination of the doping level distribution in n-type GaAs using absorption mapping - Wellmann, Peter; Albrecht, A.; Künecke, Ulrike; Birkmann, Bernhard; Müller, Georg; Jurisch, M. (European Physical Journal-Applied Physics, 2004)
We present an optical technique based on absorption measurements for the determination of the charge carrier concentration and its lateral distribution in n-type doped GaAs wafers. Calibration plots were determined in the charge carrier concentration range of 3x10(17) m(-3)...1x10(18) cm(-3) (range of trust up to 3x10(18) cm(-3)) which is technically relevant for applications of GaAs wafers as substrate for laser and light emitting diodes. The error of the optical technique is in the range of 10%... 15% and is comparable to electrical Hall measurements. The sensitivity of the setup, i.e. smallest detectable variation of doping (and hence charge carrier) concentration, is less than 1% in an area of 5x5 mm(2) and about 20% across the 3 inch area. Absorption mappings of the charge carrier and hence doping homogeneity are presented for n-type GaAs:Si and GaAs:Te.
Keywords: III-V semiconductors; Optical properties of bulk materials and thin films; Semiconductors; charge carrier concentration; absorption; mapping